Burnout y coronavirus: los efectos de la pandemia en estudiantes universitarios - D´Amelio, Adriana Graciela; Nardechia, Lucía; Tari, Johana Gisel (2020)
Fil: D´Amelio, Adriana Graciela. Universidad Nacional de Cuyo; Argentina.